Simulation tools in enhancing metal casting productivity and quality: A review. (October 2016) - Khan, Muhammad Azhar Ali; Sheikh, Anwar Khalil
Casting simulation softwares are increasingly being used in modern foundries and metal casting industries. Softwares simulate the casting process in a virtual domain and provide insight into mold filling, solidification and cooling, and casting defects. Casting simulations allow designers to model, verify, and validate the process followed by optimization of design and process parameters before they actually put into practice. This article aims at exploring the methods of modeling and simulation of metal casting processes with reference to some related case studies. Most commonly available casting simulation softwares and the underlying mathematical models used are briefly introduced. Casting process simulation together with the results obtained is well explained. Case studies from the literature revealed that simulation tools are playing a vital role in producing high-quality defect-free cast products by providing an in-depth understanding of mold filling and solidification, gating, runner and feeding system design, and other process parameters. Recent efforts on integrating the casting simulations to mechanical performance simulations are discussed which is quite promising in predicting the service life of cast products. It is concluded that simulations have been well established in metal casting processes and more developments in simulation tools are needed for reliability prediction of castings.